THE USE OF ACCOUNTING AND INTERNAL CONTROL SYSTEM DATA IN AUDIT (International Congress on Economics, Management and Business Studies, 2026)
In the process of auditing, the auditors are satisfied that the activities of the audited entity are timely recorded in documents and accounts, the value of economic transactions corresponds to the actual indicators, the economic transactions comply with the requirements of the current legislation and the rules of accounting policy, the accounting and financial statements of the enterprise are provided with the reflection of the results of economic transactions, which are closely related The company's accounting system can be assessed as reliable. When studying the accounting system of the audited entity, the following information of the enterprise is studied (Fig). The figure below shows the sources and factors used to study the reliability of an accounting system. These resources will assist the auditor in assessing the correctness and reliability of an entity's internal control system and credentials.